In-hospital and 1-year outcomes of patients without modifiable risk factors presenting with acute coronary syndrome undergoing PCI: a Sex-stratified analysis - Sheikhy, Ali; Fallahzadeh, Aida; Jameie, Mana; Aein, Afsaneh; Masoudkabir, Farzad; Maghsoudi, Milad; Tajdini, Masih; Salarifar, Mojtaba; Jenab, Yaser; Pourhosseini, Hamidreza; Mehrani, Mehdi; Alidoosti, Mohammad; et al. (Frontiers in Cardiovascular Medicine, 2023)
Aim: A considerable proportion of patients admitted with acute coronary syndrome (ACS) have no standard modifiable cardiovascular risk factors (SMuRFs: hypertension, diabetes mellitus, dyslipidemia, and cigarette smoking). The outcomes of this population following percutaneous coronary intervention (PCI) are debated. Further, sex differences within this population have yet to be established.Methods: This retrospective cohort study included 7847 patients with ACS who underwent PCI. The study outcomes were in-hospital mortality, all-cause mortality, and major adverse cardio-cerebrovascular events (MACCE). The association between the absence of SMuRFs (SMuRF-less status) and outcomes among all the patients and each sex was assessed using logistic and Cox proportional hazard regressions.Results: Approximately 11% of the study population had none of the SMuRFs. ] months of follow-up, in-hospital mortality (adjusted-odds ratio (OR):1.51, 95%confidence interval (CI): 0.91-2.65, P:0.108), all-cause mortality (adjusted-hazard ratio (HR): 1.01, 95%CI: 0.88-1.46, P: 0.731), and MACCE (adjusted-HR: 0.93, 95%CI:0.81-1.12, P: 0.412) did not differ between patients with and without SMuRFs. Sex-stratified analyses recapitulated similar outcomes between SMuRF+ and SMuRF-less men. In contrast, SMuRF-less women had significantly higher in-hospital (adjusted-OR: 3.28, 95%CI: 1.92-6.21, P<0.001) and all-cause mortality (adjusted-HR:1.41, 95%CI: 1.02-3.21, P: 0.008) than SMuRF+ women.Conclusions: Almost one in 10 patients with ACS who underwent PCI had no SMuRFs. The absence of SMuRFs did not confer any benefit in terms of in-hospital mortality, one-year mortality, and MACCE. Even worse, SMuRF-less women paradoxically had an excessive risk of in-hospital and one-year mortality.